The process of modernization in China and Kazakhstan - Dauyen, D. B. (Journal of Oriental Studies, 2016)
The given article considers the issue of modernization in Peoples Republic of China and the Republic of Kazakhstan. Gives a general characterization of the process of modernization, shows the stages, differences and features of modernization in China and Kazakhstan. Gives a brief overview of the prerequisites to the country’s modernization.